2022
DOI: 10.3389/fonc.2022.822550
|View full text |Cite
|
Sign up to set email alerts
|

Selected Patients With Peritoneal Metastases From Breast Cancer May Benefit From Cytoreductive Surgery: The Results of a Multicenter Survey

Abstract: BackgroundEven though breast cancer is the most frequent extra-abdominal tumor causing peritoneal metastases, clear clinical guidelines are lacking. Our aim is to establish whether cytoreductive surgery (CRS) could be considered in selected patients with peritoneal metastases from breast cancer (PMBC) to manage abdominal spread and allow patients to resume or complete other medical treatments.MethodsWe considered patients with PMBC treated in 10 referral centers from January 2002 to May 2019. Clinical data inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Silencing EDI3 reduced the metastatic burden, irrespective of the route of application of cells. While it should be acknowledged that the intraperitoneal model may not be the most obvious choice to study breast cancer metastasis, intraperitoneal spread has been reported in late-stage metastatic disease, also in breast cancer [ 44 , 69 71 ]. In addition, the data from the intraperitoneal model do support our overall conclusion that targeting EDI3 reduces metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing EDI3 reduced the metastatic burden, irrespective of the route of application of cells. While it should be acknowledged that the intraperitoneal model may not be the most obvious choice to study breast cancer metastasis, intraperitoneal spread has been reported in late-stage metastatic disease, also in breast cancer [ 44 , 69 71 ]. In addition, the data from the intraperitoneal model do support our overall conclusion that targeting EDI3 reduces metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ascites, positive ascites cytology, and recognition of peritoneal lesions on CT scans provide data that can lead to the diagnosis of peritoneal metastases in breast cancer. [37][38][39][40][41][42] Although the tendency of breast cancers to spread to serosal surfaces is not as clear as that of visceral metastases, studies based on histopathological subtypes have shown that lobular carcinoma has a higher tendency to spread to the peritoneal surfaces. In another study, although there was no significant difference in the molecular subtype of the primary cancer among the 3 groups, when they examined the probability of pleural metastasis alone or as a concomitant metastasis of lung metastasis, they found a more frequent association with luminal type B.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ascites, positive ascites cytology, and recognition of peritoneal lesions on CT scans provide data that can lead to the diagnosis of peritoneal metastases in breast cancer. [37–42]…”
Section: Discussionmentioning
confidence: 99%
“…In the biggest multicenter study, Cardi et al reported 49 patients with PM from ductal and lobular breast cancer with variable molecular subtypes divided into two treatment groups: patients having CRS with or without HIPEC for curative intent versus those who had noncurative interventions including drug therapy, palliative surgery, and intraperitoneal chemotherapy. There was improved overall survival in the CRS with/without HIPEC group (89.2% vs. 6% alive at 36 months, p < 0.001) [ 1 ]. However, this study included patients with incomplete CRS (CC-2, residual disease 2.5 mm-2.5 cm), the presence of preoperative extraperitoneal metastases in the CRS group, and the utilization of HIPEC based on each center’s policy.…”
Section: Discussionmentioning
confidence: 99%
“…With many therapeutic advancements in recent decades, metastatic breast cancer is usually well managed with hormonal therapy, chemotherapy, radiation, and supportive care in the majority of patients. However, there may be a subgroup of patients with isolated metastatic disease that can benefit from surgery to achieve disease control [1][2][3].…”
Section: Introductionmentioning
confidence: 99%